Preparation of Reference Material for Trigonelline Determination Inside of Green Coffee Beans Using HPTLC - Yeni M. Muflihah; Buchari Buchari (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2013)
Preliminary study of preparation reference material for trigonelline determination in green coffee beans have been performed by HPTLC method. Physical characterization performed on green coffee beans include the determination of moisture content, ash content and metal content. Water content values obtained on average 6.4% (%RSD 4.8) and ash content 3.9% (%RSD 16.2). Metal determination (Cu, Zn, Fe) with atomic absorption spectrometry method found Cu 9.4 (mg/kg), Zn 12,0 (mg/kg) and Fe 64.0 (mg /kg). Sonication as extraction method using methanol solvent for 30 minutes and separation method HPTLC on aluminum plates coated with silica gel 60 F254. Eluent used was mixture of n-propanol: methanol: water (4:1:4, v/v/v) with elution length 8 cm. Linear regression obtained in concentration range 200-1200 ng spot-1 with R2 = 0.9857. Detection limits obtained 140.7 ng and 468.9 ng for quantitation limit. Repeatability was achieved from 800 ng spot-1 (% RSD 13.8). Keywords : Reference material, Trigonelline, green coffee, HPTLC